CONSTRUCTION OF CUSTOMER RELATIONSHIP MANAGEMENT IN RETAIL BUSINESS - Robert Kristaung; Murtanto Murtanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This article aims to construct the dimensions of customer relationship management (CRM), which consists of processes, preferences, customization, readiness, and capability in the retail service industry. With a total sample of 257, the results of testing using Structural Equation Modelling show that the fifth dimension of CRM construction contributes significantly to the construction of CRM.The findingsof the study on the construction of CRM customizationshow that there is still a weaknesses in registering valuable loyal customers. The collapse of conventional retail business is caused by not putting the priority of detecting valuable old customers This weaknessbecomes the strength of online retailers who are able to get traditional retail customers to switch to online platforms. CRM customization is also a crucial managerial implication for conventional, digital retailers and digital-conventional retail formats.